Femoropopliteal Bypass with Varicose Greater Saphenous Vein - Mun, Yun Su; Cho, Byung Sun; Jang, Je-Ho; Lee, Moon-Soo; Kwon, Oh Sang (International Journal of Angiology, 2016)
Surgical bypass for peripheral arterial occlusive disease can be performed using different graft materials. Autogenous greater saphenous vein (GSV) is the treatment of choice because of its superior long-term patency. We report a case of femoropopliteal bypass with varicose GSV in a 77-year-old man who was presented with limb ischemia and both varicose veins. We successfully performed bypass with varicose vein. He has been doing well for 15 months after the operation, and a computed tomography angiography of the lower leg, performed on the 15th postoperative month, demonstrated widely patent femoropopliteal bypass graft and no structural change.
Keywords: femoropopliteal bypass; greater saphenous vein; varicose vein